Diet therapy in sepsis patients: a review (Research, Society and Development, 2020)
Sepsis is defined as an infection accompanied by systemic inflammation. It is considered a serious public health problem in the Intensive Care Unit (ICU), which despite a huge research effort in recent decades remains a considerable and growing challenge to health care. Given the above, this article presents the objective of conducting a literature review on diet therapy for sepsis patients. This study is a narrative review, covering scientific articles, monographs, theses and dissertations published in the databases: CAPES, SciELO and Google Scholar. Through the studies, it is verified that, considering the real metabolic increase of sepsis, nutritional therapy should have its early establishment, aiming to assist in the healing process, decrease of catabolic response and improvement of the structure and functionality of the gastrointestinal tract. Finally, it can be concluded that the main objective of the study can be achieved regarding the analysis of diet therapy in patients with sepsis.